IMPLEMENTASI SUPERVISI AKADEMIK PADA MADRASAH IBTIDAIYAH KABUPATEN TANAH DATAR - Syafruddin Syafruddin (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
The background in this research is the performance of teachers at Madrasah Ibtidaiyah in Tanah Datar District is still less than the maximum. Implementation of academic supervision at Madrasah Ibtidaiyah in Tanah Datar District, constrained by several things, including the plans made by the teachers are not in accordance with the implementation, time constraints supervisors and headmaster in carrying out supervision and there were some who did not complete the administrative requirements for learning devices. The purpose of researchers doing this study is to describe and analyze the academic supervision in the form of Madrasah Ibtidaiyah in Tanah Datar District and to describe and analyze the implementation of the academic supervision in the form of Madrasah Ibtidaiyah in Tanah Datar District.